2021
DOI: 10.1093/ee/nvab046
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Cost of Chlorpyrifos Resistance in Spodoptera frugiperda (Lepidoptera: Noctuidae) on Different Host Plants

Abstract: Spodoptera frugiperda (J. E. Smith, 1797) is a polyphagous pest of global relevance due to the damage it inflicts on agricultural crops. In South American countries, this species is one of the principal pests of maize and cotton. Currently, S. frugiperda is also emerging as an important pest of soybeans and winter cereals in Brazil. Chemical control is one of the main control tactics against S. frugiperda, even though resistance against numerous modes of action insecticides has been reported. To support insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…41 From F 2 to F 8 , early L3 larvae were exposed to selection pressure at a single dose of 3200 ppm of chlorpyrifos (Lorsban 480 BR) diluted in water and applied over the diet surface [equivalent to 51 μg active ingredient (a.i.) cm −2 ] as described by Garlet et al 42 From F 9 to F 15 , the selection process was performed in topical bioassays using technical grade chlorpyrifos (98% purity; Sigma Aldrich, São Paulo, SP, Brazil) diluted in acetone (99.5% purity; Sigma Aldrich) at a single dose of 10 μg chlorpyrifos per larva. This concentration was applied to the dorsal thoracic region of early L3 larvae (1 μL per larva) using a hand microapplicator (Burkard Manufacturing, Rickmansworth, UK).…”
Section: Selection and Toxicological Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…41 From F 2 to F 8 , early L3 larvae were exposed to selection pressure at a single dose of 3200 ppm of chlorpyrifos (Lorsban 480 BR) diluted in water and applied over the diet surface [equivalent to 51 μg active ingredient (a.i.) cm −2 ] as described by Garlet et al 42 From F 9 to F 15 , the selection process was performed in topical bioassays using technical grade chlorpyrifos (98% purity; Sigma Aldrich, São Paulo, SP, Brazil) diluted in acetone (99.5% purity; Sigma Aldrich) at a single dose of 10 μg chlorpyrifos per larva. This concentration was applied to the dorsal thoracic region of early L3 larvae (1 μL per larva) using a hand microapplicator (Burkard Manufacturing, Rickmansworth, UK).…”
Section: Selection and Toxicological Bioassaysmentioning
confidence: 99%
“…Using topical bioassays as previously described, cross-resistance patterns were evaluated to acephate (99.5% purity; Sigma Aldrich), methomyl (98% purity; Sigma Aldrich), and thiodicarb (99.8% purity; Sigma Aldrich). Concentrationresponse bioassays were also carried out using diet-overlay bioassays as described by Garlet et al 42 In this bioassay method the insecticides chlorfenapyr (Pirate, 240 g a.i. L −1 ; BASF SA, São Paulo, SP, Brazil), flubendiamide (Belt, 480 g a.i.…”
Section: Functional Dominance To Chlorpyrifos In Fawmentioning
confidence: 99%
“…Chlorpyrifos is also a broadly used insecticide, having a significant share of the insecticides marketed in Brazil, and S. frugiperda is certainly under high selection pressure due to the continuous exposure to this pesticide (IBAMA, 2021)The continuous exposure of S. frugiperda to the selection pressure of this pesticide, and the steady low survival probability observed during our monitoring indicate that resistance to chlorpyrifos is associated with very high fitness costs. In fact, analysis of the fitness costs of chlorpyrifos resistance in a laboratory-selected strain of S. frugiperda, demonstrated resistance affected several biological traits at the individual and population levels (Garlet et al, 2021). The fitness costs associated with chlorpyrifos resistance in S. frugiperda is so high that Garlet et al (2021) concluded populations of S. frugiperda would restore their susceptibility to chlorpyrifos with the suspended use of the selecting agent.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, analysis of the fitness costs of chlorpyrifos resistance in a laboratory-selected strain of S. frugiperda, demonstrated resistance affected several biological traits at the individual and population levels (Garlet et al, 2021). The fitness costs associated with chlorpyrifos resistance in S. frugiperda is so high that Garlet et al (2021) concluded populations of S. frugiperda would restore their susceptibility to chlorpyrifos with the suspended use of the selecting agent. The fitness cost associated with chlorpyrifos resistance is also reported to several other insect species, and in chlorpyrifos-resistant Plutella xylostella (Lepiodptera: Plutellidae) it has been suggested to occur due the excessive energy use for the over-production of detoxification enzymes and heat shock proteins when these proteins are not required (Zhang et al, 2015;Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation